A Study on Mobile Networks and 3d Self-Deployment Algorithm (International Journal of Engineering and Computer Science, 2015)
The sensor deployment problem of wireless sensor networks (WSNs) is a key issue in the researches and theapplications of WSNs. Fewer works focus on the 3D autonomous deployment. Aimed at the problem of sensordeployment in three-dimensional spaces, the 3D self-deployment (3DSD) algorithm in mobile sensor networksis proposed. A 3D virtual force model is utilized in the 3DSD method. A negotiation tactic is introduced toensure network connectivity, and a density control strategy is used to balance the node distribution. Theproposed algorithm can fulfill the nodes autonomous deployment in 3D space with obstacles. Simulationresults indicate that the deployment process of 3DSD is relatively rapid and the nodes are well distributed.Furthermore, the coverage ratio of 3DSD approximates the theoretical maximum value